Paul & the law : a contextual approach - Thielman, Frank (Downers Grove, Ill. : InterVarsity Press, 1994)
No issue in contemporary Pauline studies is more contested than Paul's view of the law. Paul & the Law is a careful attempt to assault this crucial interpretive problem with a new strategy. Rather than taking a systematic, topical approach, Frank Thielman examines Paul's view of the law in context: the context of Judaism, the context that gave birth to each letter, and the context of each letter's language and argument. While many studies have focused on Paul's explicit statements about the law, Thielman goes further in investigating those contexts where Paul's language is allusive and his view implied.
Paul, the law & Judaism : the creation & collapse of a theological consensus -- Oppression, election & salvation : the law of Moses & the hope of Israel in the time of Paul -- Sanctified Gentiles in Thessalonica : a paradox in the Thessalonian letters -- Sanctified Gentiles in Corinth : the paradox intensifies -- Old covenant & new in the Corinthian letters : the paradox explained -- The law of Moses & the law of Christ in Galatians -- Rubbish & resource : the law of Moses in Philippians -- The law of Moses, the human plight & the law of faith in Romans 1-4 -- Old covenant sin & new covenant sanctity in Romans 5-15 -- Old convictions in new settings : the law of Moses in Paul's later letters -- Paul & the law in context.
Includes bibliographical references (p. [311]-322) and indexes.
Keywords: Bible. -- Theology; Law (Theology) -- Biblical teaching